Combating Child Trafficking Internationally and Nationally: Saudi Arabia as a Model - Khater, Maya Hasan (Journal of Economic, Administrative and Legal Sciences, 2021)
Human trafficking, especially child trafficking, due to its serious violations of human rights and fundamental freedoms in particular and its negative effects on the stability and cohesion of society in general, has recently engaged international attention.The number of persons affected by various forms of child trafficking, such as economic and sexual exploitation, forced recruitment, organ trafficking and so on, is constantly increasing worldwide. Therefore, this problem, owing to the misuse of modern technologies and techniques by organized crime groups for the exploitation of and trafficking in children, must be highlighted and given due attention at the national and international levels.
Keywords: human rights; human trafficking; child trafficking; child protection